Absence of genotoxic effects of the coumarin derivative 4-methylesculetin in vivo and its potential chemoprevention against doxorubicin-induced DNA damage - Fedato, Rafael Palhano [UNESP]; Maistro, Edson Luis [UNESP] (Wiley, 2012)
4-Methylesculetin (4-ME) is a synthetic derivative of coumarin that displays a potent reactive oxygen species (ROS) scavenger and metal chelating agent and therefore has been produced to help reduce the risk of human disease. The main objective of this study was to investigate the in vivo genotoxicity of 4-ME and initially to verify its potential antigenotoxicity on doxorubicin (DXR)-induced DNA damage. Different doses of 4-ME (500, 1000 and 2000mgkg -1 body weight) were administered by gavage only or with a simultaneous intraperitoneal (i.p.) injection of DXR (80mgkg -1). The following endpoints were analyzed: DNA damage in peripheral blood, liver, bone marrow, brain and testicle cells according to an alkaline (pH>13) comet assay and micronucleus induction in bone marrow cells. Cytotoxicity was assessed by scoring polychromatic (PCE) and normochromatic (NCE) erythrocytes (PCE/NCE ratio). No differences were observed between the negative control and the groups treated with a 4-ME dose for any of the endpoints analyzed, indicating that it lacks genotoxic and cytotoxic effects. Moreover, 4-ME demonstrated protective effects against DXR-induced DNA damage at all tested doses and in all analyzed cell types, which ranged from 34.1% to 93.3% in the comet assay and 54.4% to 65.9% in the micronucleus test.
Keywords: 4-methylesculetin; Antigenotoxic effects; Comet assay; Coumarin derivative; Micronucleus test